2013
DOI: 10.1128/jcm.02751-12
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Storage Does Not Affect the Quantitative Yield of Mycobacterium tuberculosis in Sputum in Early-Bactericidal-Activity Studies

Abstract: dEarly-bactericidal-activity (EBA) studies measure the change in mycobacterial load in sputum over time to evaluate antituberculosis drugs. We investigated whether a delay in sputum processing influences the quantitative results of sputum mycobacterial culture. We identified pretreatment smear-positive sputum samples collected overnight and processed at a single laboratory. Sputum volume, time from sputum collection to processing, CFU counts/ml of sputum, and time to culture positivity (TTP) data were retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…This might lead to an interval of several days before sputum specimens are delivered to the laboratory with a likely loss of viability of a proportion of bacilli and an increased risk of contamination. This was recently evaluated during series of EBA studies during which 817 TTP and 794 CFU results were processed [68]. Time elapsed before processing varied from 0 to 3 days and specimens were maintained on ice at 2-8˚C when any delay occurred in processing of the specimen.…”
Section: Transport and Storage Of Sputum Before Analysismentioning
confidence: 99%
“…This might lead to an interval of several days before sputum specimens are delivered to the laboratory with a likely loss of viability of a proportion of bacilli and an increased risk of contamination. This was recently evaluated during series of EBA studies during which 817 TTP and 794 CFU results were processed [68]. Time elapsed before processing varied from 0 to 3 days and specimens were maintained on ice at 2-8˚C when any delay occurred in processing of the specimen.…”
Section: Transport and Storage Of Sputum Before Analysismentioning
confidence: 99%
“…If transport to the laboratory is delayed by Ͼ1 h, specimens should be refrigerated at 4°C as well as upon arrival in the laboratory until they are processed. One study in adults showed that mycobacterial load and culture time to positivity were not significantly affected by refrigerated storage for Յ3 days (12). If prolonged storage or transport is unavoidable, preservatives can be added to the specimens to inhibit growth of contaminant bacteria and thus improve the yield from culture.…”
Section: Specimen Selection Collection and Transportmentioning
confidence: 99%
“…For example, a typical sputum sample of a Mycobacterium tuberculosis -infected individual may contain 10 5 –10 6 cells/ml. [7] Using RNAse inhibitors that prevent RNA degradation in the whole-cell assay may further improve the detection limit. The assay is selective, since little or no fluorescence increase was observed in the presence of RNA from a non-targeted bacterium.…”
mentioning
confidence: 99%